Coupling of lysosomal and mitochondrial membrane permeabilization in trypanolysis by APOL1 - Vanwalleghem, Gilles (Nat Commun, 2015)
Humans resist infection by the African parasite Trypanosoma brucei owing to the trypanolytic activity of the serum apolipoprotein L1 (APOL1). Following uptake by endocytosis in the parasite, APOL1 forms pores in endolysosomal membranes and triggers lysosome swelling. Here we show that APOL1 induces both lysosomal and mitochondrial membrane permeabilization (LMP and MMP). Trypanolysis coincides with MMP and consecutive release of the mitochondrial TbEndoG endonuclease to the nucleus. APOL1 is associated with the kinesin TbKIFC1, of which both the motor and vesicular trafficking VHS domains are required for MMP, but not for LMP. The presence of APOL1 in the mitochondrion is accompanied by mitochondrial membrane fenestration, which can be mimicked by knockdown of a mitochondrial mitofusin-like protein (TbMFNL). The BH3-like peptide of APOL1 is required for LMP, MMP and trypanolysis. Thus, trypanolysis by APOL1 is linked to apoptosis-like MMP occurring together with TbKIFC1-mediated transport of APOL1 from endolysosomal membranes to the mitochondrion.